2008
DOI: 10.1096/fj.08-111096
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of sonic hedgehog as a novel NF‐κB target gene that promotes NF‐κB‐mediated apoptosis resistance and tumor growth in vivo

Abstract: To explore mechanisms controlling sonic hedgehog (Shh) expression in human cancers, we investigated regulation of Shh by the transcription factor NF-kappaB. We identify putative NF-kappaB binding sites in the human Shh promoter region that specifically bind NF-kappaB complexes. Further, NF-kappaB activation by tumor necrosis factor alpha (TNF-alpha) or p65 overexpression stimulates Shh promoter activity and p65 binds to Shh promoter in vivo. NF-kappaB-mediated transcriptional activation of Shh is mapped to a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
92
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(103 citation statements)
references
References 30 publications
10
92
0
1
Order By: Relevance
“…In several cases, the regulation mechanism is known. Koga et al, 2008;Kasperczyk et al, 2009). Expression of Gli1 is reported to be regulated by TGFb, Ras, JUN, SCL/TAL1 and EWS-FLI1 oncoprotein (Ji et al, 2007;Kasai et al, 2008;Zwerner et al, 2008;Beauchamp et al, 2009;Laner-Plamberger et al, 2009;NolanStevaux et al, 2009).…”
Section: Interactions Between Hedgehog Signaling and Other Pathwaysmentioning
confidence: 99%
“…In several cases, the regulation mechanism is known. Koga et al, 2008;Kasperczyk et al, 2009). Expression of Gli1 is reported to be regulated by TGFb, Ras, JUN, SCL/TAL1 and EWS-FLI1 oncoprotein (Ji et al, 2007;Kasai et al, 2008;Zwerner et al, 2008;Beauchamp et al, 2009;Laner-Plamberger et al, 2009;NolanStevaux et al, 2009).…”
Section: Interactions Between Hedgehog Signaling and Other Pathwaysmentioning
confidence: 99%
“…Studies have shown that tumor-necrosis factor-alpha (TNF-a) and interleukin-6 (IL-6) can upregulate Shh expression and promote cell proliferation, contributing to tumor growth. 17,18 Suppression of Shh signaling by pharmacologically targeting the Smo receptor resulted in downregulation of TNF-a and IL1b mRNA expression in cholestatic rat liver. 19 Heller et al…”
Section: Discussionmentioning
confidence: 99%
“…Kasperczyk et al (41) demonstrated that the expression of transcription factors nuclear factorjB (NF-jB) and Shh was closely related and that Shh activated through NF-jB pathway activation contributed to the proliferation of pancreatic cancer and resistance to TNF related apoptosis inducing ligand (TRAIL)-induced apoptosis by analyzing Shh promoter activation. Hedgehog signaling activation in cancer tissue has also been demonstrated in breast cancer.…”
Section: Hedgehog Ligand Overexpression and Tumor Initiationmentioning
confidence: 99%
“…This result indicates that Hh signaling can suppress Wnt signaling and that Hh signaling might be implicated in colon cancer. Recently, many researchers have demonstrated crosstalk between the Hh signaling pathway and other pathways, including the NF-jB, (41) ERa, (43) KRAS, (57) PI3k-AKT, (58) EWS ⁄ FLI1, (59) PKC-delta (60) and p53 (61) pathways (Fig. 3).…”
Section: Crosstalk Between the Hh Pathway And Other Pathwaysmentioning
confidence: 99%